The Importance of Elementary Teacher Understanding: A Study of Perceptions of Disaster Education Models in Indonesia - Tengku Muhammad Sahudra; Ary Kiswanto Kenedi; Racmatsyah Racmatsyah; Hamimah Hamimah; Ciptro Handrianto (Universitas Negeri Gorontalo, 2024)
This research is motivated by the need for efforts to teach disaster principles to elementary school students, so a scientific foundation is needed regarding disaster education models for elementary school students. This qualitative descriptive research describes elementary school teachers' perceptions of the disaster education model for elementary school students. The sampling technique uses the purposive sampling technique. Data was obtained through questionnaires and interviews with 30 elementary school teachers from different schools. The data analysis technique uses data reduction, presentation, and conclusion. The data validity process is carried out using triangulation techniques. The research results show that the teacher's perception of aspects of the teaching material is in the poor category, the teacher's perception of the learning interaction aspect is in the poor category, the teacher's perception of elements of the learning environment is in the poor category, and the teacher's perception of the learning model aspect is in the poor category. This result shows that teachers need a better perception of the disaster education process for elementary school students. The findings of this research can be used as a basis for developing appropriate disaster education processes for elementary school students.